Incidence and influencing factors of subsyndromal delirium in elderly patients with pancreatic surgery: a prospective study - Xu, Hui-Qing; Wang, Yun; Xia, Ning-Ning; Pan, Kuei-Ching (Frontiers in Psychiatry, 2025)
ObjectiveTo prospectively investigatethe incidence and influencing factors of Subsyndromal delirium (SSD) in elderly patients undergoing pancreatic surgery.MethodsAccording to a prospective observational study, elderly patients (aged ≥60 years) who underwent pancreatic surgery in the pancreatic center of our hospital from August 2023 to February 2024 were selected. Patients were divided into SSD and Normal groups based on the evaluation of the Delirium Rating Scale-revised-98 in the first 1-4 days postoperatively. Multivariate logistic regression was performed to determine the influencing factors, and subject operating characteristic curves were used to assess the predictive effect of risk factors for subsyndromal delirium.ResultsA total of 179 elderly pancreatic surgery patients were included in this study. 67 elderly patients developed subsyndromal delirium with an incidence of 37.43%. Multivariable Logistic regression revealed that risk factors for SSD included age, age-adjusted Charlson Comorbidity Index (aCCI), and postoperative fever, while and education level with senior high school or above was found to be protective factors. Receiver operating characteristic (ROC) curve showed that the combination of age and aCCI predicted SSD in elderly pancreatic surgery patients (Area Under Curve = 0.815, 95% Confidence Interval: 0.752 - 0.878), with sensitivity and specificity of 80.6% and 75.9%, respectively.ConclusionThe incidence of subsyndromal delirium after elderly pancreatic surgery was as high as 37.43%. Effective assessment and prevention of subsyndromal delirium are crucial. In the early postoperative period, special attention should be given to elderly patients with more preoperative comorbidities and lower education levels, and their temperature should be monitored in a timely manner.